(untitled) (REVISTA DE ECONOMIA DA UEG, 2018)
One of the main modifications on public health politics in the late 1990, were the decentralization promoted by Federal Union, States and Municipalities as fundamental tasks conducting public health actions. This article aims to evaluate public expenditure of municipalities of Minas Gerais State by two comparative analysis: first Minas Gerais municipalities in comparison to the total Brazilian municipalities and second among the municipalities of Minas Gerais State. In the analysis of Minas Gerais municipalities, prominence is for the political parties and regional insertion. There is a low party relevance on resources allocation and some importance on federal laws besides the absence of regional standard for expenditures.